(untitled) (Diversity Research: Journal of Analysis and Trends, 2024)
In the age of information and communication of the 21st century, the sharp increase in the volume of information places special demands on the quality of the information transmitted to the students, along with the perception of the educational material. From this point of view, the improvement of learning information technologies in the transformation of students’ knowledge is one of the issues that require special attention. In the article, the author emphasized the trends in the use of digital technologies in the process of higher education